Resilience among High Risk Youth - McIntyre, Kevin; Wisconsin Clearinghouse, Madison ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This report focuses on children who are at risk for abusing alcohol and other drugs. It notes that the concept of risk factors is only one component necessary to understanding the range of youth drug-related behaviors. A second component, protective factors, is identified and defined as those aspects of a person's biology, psychology, and environment which serve to mediate or mitigate against substance abuse. These protective factors serve as the basis of this report. It begins by discussing protective factor research and providing an overview of the contributions derived from the mental health field. The analysis and research of several individuals and teams are highlighted in order to provide an understanding of how the concept of protective factors has been approached, the direction their insights have taken them, and the results they have achieved. Following this, the report considers the status of protective factor research in the alcohol and other drug abuse field. It is noted that several factors have been strongly identified in the literature as protective against the development of alcohol or other drug abuse; personal, social, and familial factors are listed. A third section explores issues related to protective factor research. The concluding section considers the implications of protective factor research for social policy and for prevention programming. (NB)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescents; Alcohol Abuse; At Risk Persons; Children; Drug Abuse; Resilience (Personality); Youth Problems; Information Analyses